Running Event “Trackpresso: 5K Color Run 2024 di Kota Semarang, Jawa Tengah” sebagai Event Manager dan Sponsorship Manager - Rahmanuz Zidan, Aimar; Naryoso, Agus; Manalu, S. Rouli (Interaksi Online, 2024)
This project focuses on the comprehensive preparation and execution of the Trackpresso: 5k Color Run 2024 event. Anak Panah Kopi, as the client, collaborated with the project team due to a desire to create an event that aligned with recent popular trends. This project report is based on the event management framework outlined in Joe Goldblatt's book "Special Events," which details the five stages of event planning, from research to evaluation. The Trackpresso: 5k Color Run aimed to attract 150 participants on August 24th in Semarang. The results of this report demonstrate that the event was executed in accordance with the predefined targets. A total of 150 participants joined the Trackpresso: 5k Color Run. As the Event Manager and Sponsorship Manager, we successfully achieved the set targets, including the participation of 150 participants and securing sponsorship worth Rp 35,682,500.Additionally, other targets such as the number of volunteers, government permits, the Strava challenge program, and sponsorship achievements were met. This report recommends that the Trackpresso: 5k Color Run project can contribute academically to the preparation of similar events.